STATE SOVEREIGNTY AND SELF-DEFENCE IN CYBERSPACE - Pallavi Khanna (BRICS Law Journal)
Given the increasing role and use of cyberspace in our daily lives, it is important to consider the large-scale dynamics of the cyber forum. Shifting the focus from individuals to nation states as participants that engage in activities in cyberspace raises doubts over the status of nations in this domain. Do they continue to remain sovereign entities on such a platform? Do they have the right to defend themselves against attacks from other nations? These questions have been subject to a lot of debate in the context of international law. The aim of this paper is to study the implications of the principle of state sovereignty and selfdefence in cyberspace. The paper focuses on two prime considerations of sovereignty and self-defence in the context of cyberspace and its link to international law. Thus the scope is limited to concepts such as territorial jurisdiction, sovereignty, attribution and selfdefence. While doing so, the researcher seeks to answer questions such as, Is international law applicable to cyberspace? Can cyberspace be called a sovereign domain? Do principles of territorial jurisdiction apply to cyberspace? How does the attribution mechanism work in cyberspace? Under what circumstances are states permitted to exercise the right of self-defence against cyber attacks? and What are the deficiencies in international law governing cyberspace?